(untitled) (Bangladesh Journal of Otorhinolaryngology, 2009)
Necrotizing Fasciitis of head -neck is not so uncommon in diabetic patients which is a progressive, destructive and potentially life threatening soft tissue infection primarily affecting superficial fascial planes. It is caused by group A streptococci or by a synergistic combination of aerobe and anaerobe micro organisms. This is a retrospective study which makes an attempt to analyze various parameters such as demography, aetiology, complications, and management methods determining the overall prognosis. Odontogenic infection was the primary source of infection. Diabetes, anaemia, chronic renal failure and electrolyte imbalance were the most commonly associated illness. Surgical debridement with combined antibiotic therapy was used in the management of necrotizing fasciitis along with good control of diabetes and correction of anaemia and electrolyte imbalances. Overall mortality was low. The late referral and associated complications had increased the hospital stay. With proper control of infection by early diagnosis, surgical debridement and combined antibiotic therapy, along with timely control of complications and associated illness - better results can be possible. Key words: necrotizing fasciitis, antibiotics, debridement DOI: 10.3329/bjo.v14i1.3274 Bangladesh J of Otorhinolaryngology 2008; 14(1) : 9-14